Marketing Management, Global Edition - Kotler, Philip; Keller, Kevin Lane (Pearson International Content, 2022)
Start thinking like a marketer with the gold-standard text for today's Marketing Management. Marketing Management, 16th edition by Kotler, Keller, and Chernev, is the latest version of this landmark text, offering an extensive analysis of the latest theories and practices in the marketing environment. Ideal for undergraduates and graduates who want to follow a career in the field, the book introduces you to the Marketing Manager's way of thinking, focusing on the role, issues, and decisions that Managers face in alignment with company needs and objectives. The text's reader-friendly content provides balanced coverage and a clear structure that will guide you through the necessary steps to build, execute and manage successful marketing campaigns and compelling brands. The latest edition uses a multidisciplinary approach, providing in-depth knowledge and broader understanding of the essential marketing principles and core concepts. It will challenge your critical thinking and analytical skills with universal practical applications, covering a wider spectrum of products, services, and marketing strategies. A range of examples includes Wegmans, Starbucks, and Uniqlo, bringing first-hand experience regarding how a successful marketing strategy works in large-scale organisations. Reflecting recent changes and developments in the field, the book aims to provide an in-depth understanding of the best marketing practices and arm you with the knowledge and tools necessary for a successful future career in the field. Pearson MyLab® Marketing is not included. Students, if Pearson MyLab Marketing is a recommended/mandatory component of the course, please ask- your instructor for the correct ISBN. MyLab Marketing should only be purchased when required by an instructor. Instructors, contact your Pearson representative for more information.